(untitled) (Proceedings of International Educators Conference, 2023)
Our corpus-based approach allows us to analyze trends in proper noun translation and illustrate our point of view. A detailed study (hereinafter) of all examples of proper names present in our corpus will allow us to create a work of formal and detailed description of the morphological features of proper names in the source and target languages. This information can be of great help to the translator who is having difficulty translating proper nouns.